Exploring the feasibility and potential mechanism of synergistic enhancement of sludge dewaterability by ultrasonic cracking, chitosan re-flocculation and sludge-based biochar adsorption of water-holding substances. Issue 5 (October 2022) - Yang, Yahong; Yang, Xingfeng; Yang, Qiyong; Zhang, Huining; Xu, Weixin; Zhu, Lifan; Ma, Pengjin; Li, Yangying
Abstract: A method based on sludge-based biochar (SBB) skeleton adsorption of water-holding substances coupled with ultrasonic (US) cracking and chitosan (CTS) re-flocculation was proposed to strengthen sludge dewatering. Combined conditioning can greatly improve the sludge dewatering performance, the specific resistance to filtration (SRF), capillary suction time (CST), cake moisture content (MC) of sludge were reduced by 92.98 %, 78.46 %, 16.35 %. By analyzing the Zeta potential, relative hydrophobicity, water distribution, particle size distribution, filtrate organic matter, and extracellular polymeric substances (EPS) composition and structure of sludge, it was found that US, CTS and SBB showed significant synergistic effects. US disintegrated sludge flocs and promoted the transformation of functional groups on EPS, breaking the bond between solid and water molecules, releasing some bound water and intracellular substances, which laid the foundation for SBB to adsorb water-holding substances. CTS reconstituted flocs and crosslinked with protein (PN) to form complexes, which changed the spatial conformation of proteins. SBB adsorbs the water-holding substances such as protein and polysaccharide (PS) released in the outer EPS, promotes the dissolution of inner EPS, further promotes the denaturation and transformation of protein secondary structure, and improves the hydrophobic expression of sludge. Moreover, the combined conditioning reduces the compressibility of sludge and improves the water filtration efficiency. US+CTS+SBB is a green and promising combination technology, which has a certain reference value for sludge deep dehydration. Graphical Abstract: ga1 Highlights: US, CTS and SBB can jointly enhance the sludge dewaterability. US cracking sludge floc release bound water, providing more binding sites for CTS. CTS cross-linked with protein, reducing the hydrophilic organic matter. SBB adsorbs water-holding substances and strengthens the hydrophobic expression. Combined conditioning promotes the denaturation of protein secondary structure.